2020
DOI: 10.1002/cphc.202000309
|View full text |Cite
|
Sign up to set email alerts
|

Chiral, Thermally Irreversible and Quasi‐Stealth Photochromic Dopant to Control Selective Reflection Wavelength of Cholesteric Liquid Crystal

Abstract: A chiral and thermally irreversible photochromic fulgide derivative incorporating an (R)‐binaphthol unit in its acid anhydride moiety was used for the photoswitching of the pitch length of cholesteric liquid crystals. Since the absorption maximum wavelengths of both thermally stable photoisomers are nearly in the UV region (quasi‐stealth photochromism), it can be exposed to visible light without inducing photochromic reactions. Therefore, when the photoswitching molecule is added to a permanent cholesteric liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 72 publications
0
1
0
1
Order By: Relevance
“…D. Manaila-Maximean et al reported polymer-dispersed CLCs reflecting in the infrared region using the photopolymerization-induced phase separation method [ 32 ]. A photoresponsive CLC composed of photoresponsive chiral photochromic dopant, non-photoresponsive chiral dopant, and nematic LCs was prepared, and the CLC exhibited color change between red and blue upon ultraviolet light irradiation [ 33 ]. A photochromic and thermochromic CLC of colorful patterns was achieved by synthesizing a chiral dopant with trans-p-hexoxycinnamic acid [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…D. Manaila-Maximean et al reported polymer-dispersed CLCs reflecting in the infrared region using the photopolymerization-induced phase separation method [ 32 ]. A photoresponsive CLC composed of photoresponsive chiral photochromic dopant, non-photoresponsive chiral dopant, and nematic LCs was prepared, and the CLC exhibited color change between red and blue upon ultraviolet light irradiation [ 33 ]. A photochromic and thermochromic CLC of colorful patterns was achieved by synthesizing a chiral dopant with trans-p-hexoxycinnamic acid [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…[79] Sowohl die thermischen Eigenschaften [85] dieses und ähnlicher Systeme, als auch die Zyklisierungs- [86] und Ring-Öffnungsreaktion [87] wurden in den letzten Jahrzehnten eingehend untersucht. [88][89] [90] Daneben stellt die besonders geringe Schaltermüdung (Photo-Fatigue) beim Großteil der Verbindungen dieser Substanzklasse auch nach mehreren tausend Schaltzyklen einen besonderen Vorteil dar. [79] Verschiedenste synthetische Modifikationen wie z.B.…”
Section: Azobenzol-photoschalterunclassified